Review of Conformity on ESP Course Syllabus According to Students Need Analysis - Hapsari, Fitri Senny; Frijuniarsi, Nurul (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2024)
This research aims to evaluate the appropriateness of the Informatics English syllabus as an English for Specific Purposes (ESP) course, informed by a needs analysis of students in the Computer Engineering degree. In the age of globalization and swift technological progress, mastery of English has become progressively vital for students, particularly in a professional setting. Despite the current syllabus was crafted to adhere to academic requirements, evaluation outcomes indicate that it inadequately addresses the distinct needs of the students. The employed research method is a qualitative approach that involves students as the primary participants in the needs analysis process. Data were gathered via surveys and interviews with second-semester students to ascertain the English language skills considered essential by students for their employment in computer technology. The research findings reveal that students prioritize reading and writing skills over speaking and listening skills, highlighting a discrepancy between the syllabus's learning objectives and the students needs. These studies aim to offer ideas for enhancing the ESP course syllabus, so increasing its relevance and efficacy in equipping students to confront workforce issues. Consequently, this research aids in the formulation of a curriculum that is more attuned to the students' need and the industry.